Record keeping in psychotherapy and counseling : ethics, practice and supervision - Luepker, Ellen T. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Record Keeping in Psychotherapy and Counseling: Ethics, Practice and Supervision, grounded in contemporary challenges, emphasizes protecting the therapeutic and supervisory relationship through offering an essential framework for thoughtful record keeping within legal, ethical, supervisory and clinical contexts. A reader-friendly conversational style plus compelling case examples from a variety of settings-- clinic to courtroom- bring dilemmas and strategies to life. New case studies invite readers to examine principles of ethical decision-making in order to reach sound decisions, meeting a critical need in training and continuing education. New material on telehealth and updated material on electronic records, the impact of digital communications, and experience implementing HIPAA, bring this book up to date. Sample forms for readers' use and modification are available on the publisher's website. Practitioners in all mental health disciplines, from students to seasoned clinicians, supervisors, and teachers will continue to rely on this book for protecting themselves, their patients, and their trainees"--
Keywords: Psychiatric records; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Applied Psychology